Decision Enhancement Services Rehearsing the Future for Decisions That Matter - Keen, Peter G.W (IOS Press, 2013)
The photographs above show four very typical decision-making meetings in progress. All of them make use of information technology – computers and telecommunications links. But the photographs tell us nothing about the IT contribution to the decision process. Nor can they tell us about the quality of the decision process.